Assessment of Seasonal Variations in GNSS Errors over UAE - Abu Dhabi Case Study - A. Alnaqbi; M. M. Yagoub; A. Hasbi (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
Global navigation satellite systems (GNSS) play a vital role in daily applications. This includes precise surveying and mapping, platform navigation by sea, land, and air, monitoring of large structural deformations, and recreational applications. However, the accuracy requirements vary from user to user based on their needs and applications. The accuracy of GNSS depends on numerous factors and is impacted by different error sources, such as tropospheric delay and ionospheric error, from the moment the signal leaves the GNSS satellite until it reaches the receiver antenna of the end user. These errors are classified into three major components: satellite, propagation, and receiver errors. This study assessed the seasonal variations in GNSS errors over Abu Dhabi in the United Arab Emirates. The analysis was based on historical continuous operating reference stations (CORSs) readings for 2018. Two different software were used to derive the final coordinates of two Abu Dhabi CORS stations observed for three days every month in 2018. The results indicated variations between −3 mm and 3 mm in the horizontal components and −16 mm and 12 mm in the vertical components for the Abu Dhabi station for all days of 2018. In contrast, the horizontal component of Madinat Zayed station varied between −2 mm and 4 mm and −8 mm and 9 mm in the horizontal and vertical components, respectively. The Positioning error was larger during summer than during winter; this may be primarily attributed to the ionospheric effect.